Pelaksanaan Pembelajaran Berbasis Data, Informasi Knowledge dan Wisdom Hasil Riset Mata Pelajaran PAI: Penelitian - Rizqah Fadhilah Bula; Kasim Yahiji; Yanty K. Manoppo; Burhanuddin AK. Mantau (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the implementation of data, information, knowledge, and wisdom-based learning in Islamic Religious Education and its impact on the development of students' character and understanding of religion. Data-based learning is intended to tailor the material to the individual needs of students, while relevant and contextual information helps students understand religious values more deeply. Furthermore, wisdom in teaching decision-making plays a crucial role in shaping students' positive character. The results of the study indicate that the application of data, information, knowledge, and wisdom-based learning can create a learning environment that effectively supports the development of students' character and religious understanding. Holistic learning, integrated through educational elements such as objectives, educators, students, educational tools, and the learning environment, has a positive impact on enhancing the quality of religious education and character formation. This study provides new insights into strengthening by optimizing the use of data, information, and wisdom in teaching.